EFEKTIVITAS PENGGUNAAN "METODE TATA (TALAQQI DAN TAKRIRI)" TERHADAP KEMAMPUAN MENGHAFAL AL-QUR'AN SISWA SEKOLAH DASAR - Ahmad Puajen, - (2022)
This study focuses on proving the effectiveness of using the TATA method (Talaqqi and Takriri) on the ability to memorize the Qur'an. With the background of the quality of the ability to memorize the Qur'an of students who are still in the low category. The research method used is Quasi Experiment with a population of class V SD Negeri 3 Sukawangi, Singajaya District, Garut Regency as many as 40 students with a sampling technique in the form of non-probability - purposive sampling through details of class VA as many as 20 students as an experimental group and class VB as many as 20 participants. educated as a control group. Data collection techniques using tests. The research instrument uses a test sheet with 4 item numbers as an indicator of the ability to memorize the Qur'an and the stages of instrument development have been carried out. Based on the results of data analysis through hypothesis testing using t-test (Compare means - Independent sample t-test) and obtained a significance result of 0.000 with a significance level of 5% and obtained a thitung of 12,251 with a significance level of 5%, a ttabel score of 2.024 was obtained. Thus, the use of the TATA method (Talaqqi and Takriri) is effective on the ability to memorize the Al-Qur'an of elementary school students due to an increase in students' ability to memorize the Qur'an significantly than the ability to memorize the Qur'an of students without using the TATA method ( Talaqqi and Takriri).